Veno-arterial extracorporeal membrane oxygenation and prolonged use of mechanical compression device combine for good outcome after hypothermic cardiac arrest: a case report - Trethowan, Brian; Michaud, Christopher J.; Kumar, Anupam; Strotbaum, Ashley; Berjaoui, Wael; Spurlock, David (Journal of Emergency and Critical Care Medicine, 2019)
The use of mechanical compression devices to deliver chest compressions in conjunction with veno-arterial extracorporeal membrane oxygenation (VA ECMO) in the setting of cardiac arrest is growing. Herein, we report a case of hypothermic cardiac arrest requiring VA ECMO and prolonged use of an external compression device. A 38-year-old morbidly obese male (BMI 66.5) was admitted after being found down by a river. The patient was hypothermic (27.4 ℃; outside temperature 4 ℃) and in active asystolic cardiac arrest. A LUCAS chest compression system (Jolife, Lund, Sweden) was placed and transesophageal echo (TEE) was performed. This revealed cardiac standstill and suboptimal placement of the LUCAS device which was repositioned under TEE guidance. After difficult VA-ECMO cannulation, LV venting was required but coagulopathy, hypothermia, and body habitus precluded immediate endovascular mechanical unloading device placement. Therefore, the LUCAS was continued. After 380 minutes of VA ECMO, 460 minutes of LUCAS device support, and gradual rewarming to normothermia, the patient was cardioverted to sinus tachycardia and an Impella CP was placed. Over the next 96 hours infusions were reduced and biventricular function normalized. The Impella CP was removed on day 7, VA ECMO on day 12, and extubation occurred on day 15. He discharged with no neurologic deficits on day 34, a right sided above knee amputation his only notable hospital complication. The combined support of an external compression device and VA ECMO allowed for return of spontaneous circulation despite a downtime greater than 100 minutes. Further, TEE guidance allowed for optimal LUCAS positioning.